Raskolnikov as a Transformed Character: Aki Kaurismäki's Adaptation of “Crime and Punishment” (1983) - Mehmet Arslantepe; Efe Önal (Галактика медиа: журнал медиа исследований, 2024)
How do motion pictures transpose the characters from a well-established literary work into a cinematic narrative, replete with their own narrative potential? Can the resulting film be regarded as an entirely new creation? To explore these questions, we have selected Aki Kaurismäki's 1983 cinematic adaptation of Fyodor Dostoevsky's Crime and Punishment.